New Archeomagnetic Directional Records From Iron Age Southern Africa (ca. 425–1550 CE) and Implications for the South Atlantic Anomaly. Issue 3 (15th February 2018) - Hare, Vincent J.; Tarduno, John A.; Huffman, Thomas; Watkeys, Michael; Thebe, Phenyo C.; Manyanga, Munyaradzi; Bono, Richard K.; Cottrell, Rory D.
Abstract: The paucity of Southern Hemisphere archeomagnetic data limits the resolution of paleosecular variation models. At the same time, important changes in the modern and historical field, including the recent dipole decay, appear to originate in this region. Here a new directional record from southern Africa is presented from analysis of Iron Age (ca. 425–1550 CE) archeological materials, which extends the regional secular variation curve back to the first millennium. Previous studies have identified a period of rapid directional change between 1225 and ∼1550 CE. The new data allow us to identify an earlier period of relatively rapid change between the sixth and seventh centuries CE. Implications for models of recurrent flux expulsion at the core‐mantle boundary are discussed. In addition, we identify a possible relationship of changes recorded in these African data with archeomagnetic jerks. Plain Language Summary: Earth's dipole magnetic field is presently undergoing a rapid decay, best expressed by a deepening area of low field called the South Atlantic Anomaly (SAA). This apparent collapse of the geomagnetic field, and speculation about a future field reversal, has captured the public imagination. But we know little about the history of the SAA, limiting our ability to place current changes within a long‐term context. Here we present a new magnetic record from sites of southern Africa. The new record supports our prior inferences that the SAA is just the most recent manifestation of a recurring phenomenon in the core beneath Africa—called flux expulsion—that is having a profound impact on the expression of the geomagnetic field. Key Points: New archeomagnetic directions from the Iron Age (425–1550 CE) of southern Africa Directional changes suggest recurrent flux expulsion at the core‐mantle boundary Relationship with archeomagnetic jerks and a long‐lived South Atlantic Anomaly is identified